The Ambivalent Place of Leonardas Gutauskas in the Field of Lithuanian Literature - Vasiliauskas, Saulius (Colloquia, 2018)
Leonardas Gutauskas (b. 1938) is a well-known Lithuanian artist, poet and prose writer, who began his career in the1960s, an important decade in the development of Lithuanian literature. Noted for his Christian stance and opposition to political oppression, his refusal to appease the censors, Gutauskas worked as an authentic creator in the field of Lithuanian literature during the Soviet period, with his work being favourably received by the critics. A film based on his famous novel A Wolf Tooth Necklace and with the same title was made in 1997.Even though Gutauskas’s critical reception and other factors contributing to his prestige (for example, prizes, the sale of his paintings) are not markedly different from those of other artists who were more readily ‘sanctified’ or canonized, he did not become a representative figure of his generation, neither as a poet nor as a prose writer did he become firmly represented in Lithuanian language and literature school programmes, nor was his work put on permanent display in the National Art Gallery. This is why in this article, using Pierre Bourdieu’s theory of the sociology of literature, separating out Gutauskas’s main roles – Gutauskas as poet, Gutauskas as artist, Gutauskas as prose writer – consideration is given as to how Gutauskas’s specific, ambivalent position was formed, as to how the positions taken in the fields of art and literature interact, what effect the labels pinned on him by critics, such as ‘a dual / double / multi-faceted talent’, ‘an artist who also writes’, could have had on the reception of Gutauskas’s work.
Keywords: Leonardas Gutauskas; sociology of literature; Pierre Bourdieu; field of Lithuanian literature; symbolic capital.